Circuitos curtos de comercialização por meio de cestas agroecológicas: sustentabilidade socioeconômica na agricultura familiar - Contrigiani, Ariele Carolina (2021)
In recent years, it has been a growing weakening of public policies for the disposal of products and investment in family farming. This fact hindered and directly affected the production process and, for many families of family farmers, the only marketing channel they accessed. Today, experiences of groups of farmers and cooperatives continue to be created and they propose and use short circuits as a form of marketing, recognizing the role of the family farmer in the development of more sustainable food systems. This research aims to investigate the changes that commercialization, via short circuits through agro ecological baskets, reflected in the lives of farmers belonging to the Cooperflora Cooperative linked to the Landless Rural Workers Movement (MST) and established in the Sustainable Development Project (PDS) of the Milton Santos settlement. For this, the case study was chosen as methodological support, being a research of a descriptive and exploratory character with quantitative and qualitative data. For the collection of primary data, semi-structured forms will be applied with Cooperflora farmers who sell agro-ecological baskets, interviews with leaders from the MST's Production, Commercialization and Environment Sector (SPCMA) and observation at meetings, assemblies, spaces to think about the composition and marketing of baskets. The dissertation is organized in the form of articles, thus constituted in general introduction, four chapters / articles and general considerations. From the analysis of the results of the set of the four articles, it is concluded that the commercialization of Agro ecological Baskets for consumption groups has the potential to re-signify the relations between farmers and consumers, making them both feel that they are members of the agro food chain, generating positive points for both sides